Magnesium status in Olympic & Paralympic athletes compared with a sedentary population and validation of a FFQ as an assessment tool for dietary magnesium intake - Killer, S. C.; Brown, R. A.; Collins, A. L. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
Magnesium (Mg) is an essential mineral involved in over 350 enzymatic reactions within the human body and plays a fundamental role in electrolyte balance, cellular growth and glucose homeostasis. Literature suggests Mg deficiencies may be prevalent within athletic populations, but it is not clear whether this is due to reduced dietary intakes or increased utilisation of Mg due to high levels of physical activity. The aims of the study were two-fold. Firstly to validate a food frequency questionnaire (FFQ) against a 4-day diet diary and to compare intakes with blood samples for its potential to predict status. Secondly, to compare dietary intakes and plasma Mg status in elite athletes compared with a sedentary population.